Engaging students by moodleing a course? Case studies at the Polytechnic of Porto–School of Engineering - Viegas, C. (2014)
This work presents a comparative study covering four different courses lectured at the Polytechnic of Porto - School of Engineering, regarding the usage of a particular Learning Management System, i.e. Moodle, and its impact on students' results. This study addresses teachers who used this platform as a complement to their courses (b-learning) and identifies some particular issues in order to potentiate students' engagement and learning. Even though positive correlation factors exist, e.g. between the number of Moodle accesses versus the final exam grade obtained by each student, the explanation behind it may not be straightforward. Mapping this particular factor to course numbers reveals that the quality of the resources might be preponderant and not only their quantity. These results point to the fact that some dynamic resources might enlarge students' engagement.